20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-2481
|View full text |Cite
|
Sign up to set email alerts
|

Towards Full Aircraft Airframe Noise Prediction: Lattice Boltzmann Simulations

Abstract: Computational results for an 18%-scale, semi-span Gulfstream aircraft model are presented. Exa Corporation's lattice Boltzmann PowerFLOW® solver was used to perform time-dependent simulations of the flow field associated with this high-fidelity aircraft model. The simulations were obtained for free-air at a Mach number of 0.2 with the flap deflected at 39º (landing configuration). We focused on accurately predicting the prominent noise sources at the flap tips and main landing gear for the two baseline configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 29 publications
(34 reference statements)
4
63
0
Order By: Relevance
“…Region 4 covers the entire aircraft model, facilitating direct comparisons with the companion computational simulations. 24,25 In this paper we present PSD results obtained from integrating the UDAMAS contour maps over the entire aircraft (Region 4). Results based on Regions 1, 2, and 3 will be presented at a later date.…”
Section: E Power Spectral Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Region 4 covers the entire aircraft model, facilitating direct comparisons with the companion computational simulations. 24,25 In this paper we present PSD results obtained from integrating the UDAMAS contour maps over the entire aircraft (Region 4). Results based on Regions 1, 2, and 3 will be presented at a later date.…”
Section: E Power Spectral Densitymentioning
confidence: 99%
“…The underlying causes for the observed reduction in gear noise (in the presence of the flap) are being investigated using the companion high-fidelity simulations that were recently completed. 24,25 The baseline spectra of Fig. 29 are repeated in Fig.…”
Section: Gear-flap Interaction Noisementioning
confidence: 99%
“…4,[6][7][8][9][10][11] Additional validation studies performed with PowerFLOW can be found here. [12][13][14][15][16][17] …”
Section: Methodsmentioning
confidence: 98%
“…PSD results from Regions 1 and 4 have been used to facilitate direct comparisons with the companion computational simulations. 19,20,21 In this study mostly sample spectra obtained from integrating the UDAMAS contour maps over the wing-flap area (Region 1) are shown. Results based on integration of Regions 2, 3, and 4 are presented occasionally to reinforce certain trends.…”
Section: Noise Abatement Conceptsmentioning
confidence: 99%